The Lizzie McGuire movie - Rogow, Stan.; Jansen, Susan Estelle; Decter, Ed, 1959-; Strauss, John J., 1957-; Fall, Jim.; Duff, Hilary, 1987-; Lamberg, Adam, 1984-; Carradine, Robert, 1954-; Todd, Hallie, 1962-; Thomas, Jake, 1990-; Zielinski, Jerzy, 1950-; Goodspeed, Margie; et al. ([United States] : Walt Disney Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2003)
Lizzie, along with classmates Gordo, Kate and Ethan are celebrating with a graduation trip to Italy. Lizzie becomes mistaken for Italy's biggest pop diva and falls for her handsome singing partner. Lizzie becomes transformed from awkward teen to international pop star. But will becoming Italy's next pop sensation mean leaving her family and friends behind?
English track: Dolby digital 5.1.
Special features: "In the recording studio with Hilary" - an exclusive sneak peek at the making of her new solo album; "Off the cutting room floor" - deleted scenes, including a never-before-seen alternate ending; "Hilary's Roman adventure" - behind-the-scenes tour of the movie hosted by Hilary; Hilary's new music video "Why not"; "Roamin' Volare" - Lizzie and Paolo rock the streets of Rome music video-style.
Director of photography, Jerzy Zielinski ; editor, Margie Goodspeed ; music, Cliff Eidelman ; production designer, Douglas Higgins.
Hilary Duff, Adam Lamberg, Robert Carradine, Hallie Todd, Jake Thomas.
MPAA rating: PG.
DVD.
Keywords: McGuire, Lizzie (Fictitious character) -- Drama; Singers -- Drama; Italy -- Description and travel -- Drama; Feature films; Films for the hearing impaired